Perception and Experience of Dupilumab in Atopic Dermatitis: A Real-Life Study - Antoine L; Puzenat E; Popescu D; Charollais R; Dresco F; Dupond AS; Salard D; Drobacheff-Thiebaut MC; Zanella A; Ducournau A; Gallais-Serezal I; Aubin F (Patient Preference and Adherence, 2023)
Léa Antoine,1 Eve Puzenat,1 Dragos Popescu,2 Romain Charollais,3 Flora Dresco,3 Anne-Sophie Dupond,2 Dominique Salard,4 Marie-Christine Drobacheff-Thiebaut,1 Anaïs Zanella,1 Anne Ducournau,2 Iréne Gallais-Serezal,1 François Aubin1,5 1Department of Dermatology, University Hospital, Besançon, France; 2Department of Dermatology, Hôpital Nord Franche Comté, Trevenans, France; 3Department of Dermatology, Centre Hospitalier, Vesoul, France; 4Department of Dermatology, Centre Hospitalier, Pontarlier, France; 5Inserm 1098 RIGHT, University of Franche Comté, Besançon, FranceCorrespondence: François Aubin, Centre hospitalier Universitaire, Service de Dermatologie, 3 Bd Fleming, Besançon, 25000, France, Email francois.aubin@univ-fcomte.frPurpose: There are few data on the practical use of dupilumab by the patients and on the patients’ experience with this treatment.Objective: The objective of our study was to describe the experience and perception of dupilumab treatment in patients with atopic dermatitis (AD).Patients and Methods: We conducted a multicenter retrospective observational study including adult patients with moderate to severe AD treated with dupilumab between January 2017 and December 2021. Clinical characteristics were collected and a questionnaire was sent to all patients. It consisted of different parts including the injection method and different numeric rating scales (NRS) evaluating the patient’s satisfaction and the constraints related to the treatment.Results: Eighty-two patients were included and the information was available for 77 patients who responded to the questionnaire. Injection of dupilumab was performed by a nurse in 47% (n=36) of patients and 43% (n=33) were autonomous. Injections were performed by a family member for 7 patients or by the general practitioner (1 patient). A wearing-off of the beneficial effect of dupilumab was reported by 47% of patients leading to shorten the dosing interval. In contrast, dose spacing was reported by 9 patients (11%). After a mean follow-up time of 29.7 ± 10.7 months (median: 27 months), drug survival was 72%. From the patients’ perspective, the mean patient’s satisfaction NRS score was 7.5 ± 1.8, and the constraints related to the treatment were scored at 3.1 ± 2.1 on NRS.Conclusion: Although AD treatments may contribute to the burden of the disease, dupilumab was associated with a lower burden score, likely reflecting both treatment efficacy and easy of use and patient satisfaction.Keywords: atopic dermatitis, dupilumab, real life, experience